Dramaturgi Teater Rakyat Randai di Minangkabau - Wendy HS (Jurnal Kajian Seni, 2014)
As a cultural performance, Randai traditionally organized in various ways as partof a traditional Minangkabau order adaik salingka nagari prevailing at each villagesin Minangkabau. As a folk theater, Randai always produced with distinctive-lookingdramaturgi order relating to the socio-cultural order prevailing in Minangkabau society.Based on the description dramaturgi aspects of it, seems a common thread that connectsthe various elements of the socio-cultural order Minangkabau society.Study of this paper will show that the Randai dramaturgy typically constructed based onthe existence of elements and traditional values in the range of ethnic communities in theMinangkabau of West Sumatra. Various political and social factors in the developmentof the Minangkabau people, especially friction factor of the indigenous, Islam, andthe state, has affected the order of the elements and the traditional values that buildRandai dramaturgy. As a result, aspects and positions where Randai dramaturgi inMinangkabau society today, is also changing.